PERFORMANCE ANALYSIS OF PARABOLIC SOLAR DISH COLLECTOR FOR STAINLESS STEEL AS REFLECTING MATERIALS - Sanjay Kulal1, Suraj Nikte1, Priyanka Pawaskar1, Abhishek Patil2, Balasaheb Gadade3. (International Journal of Innovations in Engineering Research and Technology, 2022)
In this research work the performance analysis of parabolic solar dish collector is done with the use of stainless steel as reflecting materials. The Parabolic Dish Solar Collector system is made for hot water production. Water is recirculating from the storage tank to the absorber tank with the help of a pump. This analysis is carried out to study variation in temperature of water in the storage tank to a maximum value. An analysis is mainly based on the reflector material. The values of useful heat gain, instantaneous efficiency, hourly thermal efficiency and overall thermal efficiency, are calculated and their variation with solar intensity and time are plotted graphically. Solar intensity is measured by solar power meter.